2010
DOI: 10.1525/sp.2010.57.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Are Some Emotions Marked "Whites Only"? Racialized Feeling Rules in Professional Workplaces

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and Society for the Study of SocialProblems are collaborating with JSTOR to digitize, preserve and extend access to Social Problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
298
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(307 citation statements)
references
References 15 publications
7
298
2
Order By: Relevance
“…Furthermore, other research suggests that those who engage in it may be viewed negatively by white colleagues and supervisors (Harvey Wingfield 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other research suggests that those who engage in it may be viewed negatively by white colleagues and supervisors (Harvey Wingfield 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that the experience of emotional labor is not only gendered but also racialized. Harvey Wingfield (2010), who studied African American professionals in a wide variety of occupations, found that men were required to suppress any display of strong emotion, lest they be considered belligerent and aggressive, and thus lose their jobs. Because African American men are marginalized by hegemonic masculinity, they are unlikely to experience the advantages of emotional labor identified in this study.…”
Section: Token Men In Trainingmentioning
confidence: 99%
“…Emotion display norms in professional settings emphasize congeniality and a pleasant workplace demeanor, and as Lively and Powell (2006) found, direct expressions of anger at work are less likely than in the family. Expressions of anger and irritation are not completely off-limits at work, but Wingfield (2010) found that African-American professionals felt more constrained than their white counterparts in their ability to express these emotions. This was particularly true of African-American men, who felt that expressions of anger or irritation would reinforce the racial stereotype of the "angry black man."…”
Section: Anger Race and Inequality At Workmentioning
confidence: 96%
“…Members of these groups have more latitude in their compliance with display norms, while compliance may be more difficult or problematic for less advantaged categories of workers. For example, although the expression of anger is discouraged in professional workplaces, African-American men feel more pressure to comply with this norm, while simultaneously experiencing more situations likely to provoke it, than their white counterparts (Wingfield 2010). Women and other workers in structurally disadvantaged positions also confront this "emotional double-bind:" They may be more likely than more advantaged workers to experience negative emotions at work, but also face more pressures to suppress these emotions (Erickson and Ritter 2001).…”
Section: Gender Race and Emotional Displaysmentioning
confidence: 99%